Development Model Of Leading Agricultural Commodities Lareh Sago Halaban - Dara Latifa; Fastabiqul Khairad; Elviati Elviati; Novfirman Novfirman; Farid Azel; Ispinimiartriani Ispinimiartriani; M. Syakib Sidqi (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to identify and develop strategies for enhancing the leading agricultural commodities in Lareh Sago Halaban District. Methodology: The study uses the Location Quotient (LQ) method and SWOT analysis to identify and analyze strategies for developing leading agricultural commodities. Results: The findings reveal that the leading agricultural commodities contributing to regional growth in Lareh Sago Halaban District include palm sugar, betel nut, tobacco, sweet potatoes, peanuts, corn, kaempferia, tomatoes, and beans. Findings: The main strategy for developing these leading agricultural commodities is to increase productivity through various recommended strategies, supported by government regulations or policies on production management, access to capital, human resource development, processing, and marketing. Novelty: This research provides insights into effective strategies for developing region-specific agricultural commodities. Originality: The study offers a detailed analysis of the strategies and government support necessary for enhancing the productivity and marketability of leading agricultural commodities. Conclusions: Enhancing the productivity of leading agricultural commodities requires a comprehensive strategy involving increased productivity, government support, access to capital, human resource development, and effective marketing.Type of Paper: Empirical Research Article